Batik Incung Industry in Kerinci 1995-2017 (Paramita: Historical Studies Journal, 2021)
Abstract: Kerinci has batik called incung developed from the beauty of incung letters (ancient Kerinci's letters). This letter was used to be used by Kerinci's ancestors to write literary works, incantation, and customary law. The medium used to write the incung letters was wood bark, bamboo, coconut leaf, and the buffalo horn. However, this research tries to discuss the development of the batik industry in Kerinci: History Perspective. The method applied in this research is one of historical research to collect, select, and test the sources of history critically so that it results in the fact of history in line with what happened in the field. The results showed that the industry's oh Incung batik started in 1995 due to the Administration of Kerinci Regency's policy as to hold a training. Meanwhile, an independent training was held by  Jaya and Iryani in Jambi, speaking of which working for three years at Batik Mas in the City of Jambi. After 3 years, they went home to develop batik with particular Kerinci. The early stage of incung batik development was not eye-catching for the local people. They still focus on agricultural matters, though, following the issuance of a leaflet of the Mayor of Sungaipenuh ordering to develop the specific motif of Kerinci, triggering the public enthusiasm in developing batik. The incung batik marketing does not only cover the area of Kerinci Regency and City of Sungaipenuh, but also it has already reached the City of Jambi, West Sumatra, Jakarta, Bandung, and Solo. Abstrak: Kerinci memiliki batik yang disebut incung yang dikembangkan dari keindahan huruf incung (huruf Kerinci kuno). Huruf ini dulunya digunakan nenek moyang Kerinci untuk menulis karya sastra, mantera, dan hukum adat. Media yang digunakan untuk menulis huruf incung adalah kulit kayu, bambu, daun kelapa, dan tanduk kerbau. Oleh karena itu, penelitian ini mencoba membahas perkembangan industri batik di Kerinci dalam Perspektif Sejarah. Metode yang digunakan dalam penelitian ini adalah salah satu metode penelitian sejarah untuk mengumpulkan, menyeleksi, dan menguji secara kritis sumber-sumber sejarah, sehingga menghasilkan fakta sejarah yang sesuai dengan apa yang terjadi di lapangan. Hasil penelitian menunjukkan bahwa industri batik oh incung dimulai pada tahun 1995 karena adanya kebijakan Pemerintah Kabupaten Kerinci untuk mengadakan pelatihan. Sedangkan pelatihan mandiri diadakan oleh Jaya dan Iryani di Jambi yang  bekerja selama tiga tahun di Batik Mas di Kota Jambi. Setelah 3 tahun, mereka pulang untuk mengembangkan batik khas Kerinci. Perkembangan awal pembatikan incung ternyata tidak begitu menarik perhatian warga sekitar. Meski begitu, mereka tetap fokus pada pertanian, menyusul keluarnya edaran dari Walikota Sungaipenuh yang memerintahkan untuk mengembangkan motif khas Kerinci sehingga memicu antusias masyarakat untuk mengembangkan batik. Pemasaran batik incung tidak hanya mencakup wilayah Kabupaten Kerinci dan Kota Sungaipenuh, tetapi juga sudah menjangkau Kota Jambi, Sumatera Barat, Jakarta, Bandung, dan Solo.